A study of morphological effect of oxygen reduction catalyst on microbial fuel cell performance - Ravinder, Kumar (2017)
Microbial fuel cell (MFC) is a promising technology that produces electricity from various organic substrates using microorganisms as biocatalysts. However, the technology is facing numerous challenges for its commercialization. One of these challenges is to replace the expensive platinum catalyst by an efficient and cost-effective cathode catalyst for oxygen reduction reaction (ORR) in air-cathode MFCs. Co3O4 (cobalt oxide) shows higher affinity towards oxygen molecules that makes it more favorable for chemisorptions of oxygen molecules onto the catalyst surface. The morphology of the catalyst plays an indispensable role in ORR activity that further affects the MFC performance. Therefore, in this research work, three different morphologies of Co3O4 that is Co3O4 nanorods, Co3O4 flakes, and Co3O4 flower were prepared by hydrothermal methods and their potential for ORR activity and electricity generation was investigated in a double-chamber MFC. The results revealed that Co3O4 nanorods showed higher ORR activity and generated the highest power density in MFC as compared to Co3O4 flakes, and Co3O4 flower, which can be attributed to higher BET surface area of the nanorods that comparatively provided more reduction sites for oxygen. Evidently, Co3O4 nanorods exhibited a BET surface area of 15.55 m²/g, which was 40% higher than the flakes (11.05 m²/g) and 209% higher than flower-like Co3O4 (5.03 m²/g). Moreover, electrochemical impedance spectroscopy (EIS) suggested that the nanorods reduced the resistance of the system significantly that enhanced the electron transfer on the cathode interfaces and increased the ORR activity and consequently, the power density. The ORR kinetics of the cathodes were studied by Tafel plots, which indicated that Co3O4 nanorods achieved the highest exchange current density that is 5.67 A/m2. This higher ORR activity of Co3O4 nanorods influenced the MFC performance and generated the highest power density of 454 mW/m2, which was 49% higher than Co3O4 flakes and 165% higher than flower-like Co3O4. These results suggested that Co3O4 nanorods showed higher ORR activity as compared to Co3O4 flakes and Co3O4 flower, therefore, the ORR activity of Co3O4 nanorods was further improved with the addition of manganese (Mn) and MnCo2O4 nanorods were prepared by a hydrothermal method and its potential for ORR activity and electricity generation was investigated in the similar MFC. The CV, LSV, and Tafel results revealed that the ORR activity of the nanorods was enhanced after the introduction of Mn, which ultimately increased the power output in the MFC and generated a maximum power density of 587 mW/m2 that was 29% higher than Co3O4 nanorods and ~500% higher than the bare cathode. The improved power output can be ascribed to the excellent ORR activity of Co2+/ Co3+ and Mn3+/ Mn4+ on the cathode surface. Therefore, this research work showed that the MFC performance can be greatly affected by the morphology of the cathode catalyst.